86.1k views
3 votes
Express the product of z1 and z2 in standard form given that
z_(1) = 6[cos((2\pi )/(5)) + isin((2\pi )/(5))] and
z_(2) = 2√(2) [cos((-\pi )/(2)) + isin((-\pi )/(2))]

Express the product of z1 and z2 in standard form given that z_(1) = 6[cos((2\pi )/(5)) + isin-example-1
User Yu Tao
by
5.3k points

1 Answer

5 votes

Answer:

Solution : 5.244 - 16.140i

Explanation:

If we want to express the two as a product, we would have the following expression.


-6\left[\cos \left((2\pi )/(5)\right)+i\sin \left((2\pi )/(5)\right)\right]\cdot 2√(2)\left[\cos \left((-\pi )/(2)\right)+i\sin \left((-\pi \:)/(2)\right)\right]

Now we have two trivial identities that we can apply here,

( 1 ) cos(- π / 2) = 0,

( 2 ) sin(- π / 2) = - 1

Substituting them,

=
-6\cdot \:2√(2)\left(0-i\right)\left(\cos \left((2\pi )/(5)\right)+i\sin \left((2\pi )/(5)\right)\right)

=
-12√(2)\sin \left((2\pi )/(5)\right)+12√(2)\cos \left((2\pi )/(5)\right)i

Again we have another two identities we can apply,

( 1 ) sin(x) = cos(π / 2 - x )

( 2 ) cos(x) = sin(π / 2 - x )


\sin \left((2\pi )/(5)\right)=\cos \left((\pi )/(2)-(2\pi )/(5)\right) = \frac{√(2)\sqrt{5+√(5)}}{4}


\cos \left((2\pi )/(5)\right)=\sin \left((\pi )/(2)-(2\pi )/(5)\right) = \frac{√(2)\sqrt{3-√(5)}}{4}

Substitute,


-12√(2)(\frac{√(2)\sqrt{5+√(5)}}{4}) + 12√(2)(\frac{√(2)\sqrt{3-√(5)}}{4})

=
-6\sqrt{5+√(5)}+6\sqrt{3-√(5)} i

=
-16.13996 + 5.24419i

=
5.24419i - 16.13996

As you can see option d is the correct answer. 5.24419 is rounded to 5.244, and 16.13996 is rounded to 16.14.

User Gluuke
by
5.7k points